First attempt to survey montane bird species using camera traps in Cameron Highlands, Peninsular Malaysia - Mohd. Top @ Mohd. Tah, Marina; Puan, Chong Leong; Baharudin, Nur Syakirah; Azizan, Aqilah Amni (Universiti Putra Malaysia, 2024)
The use of camera traps to record tropical forest bird diversity is uncommon. In 2020, over a period of 200 active camera trap days, ten camera traps were deployed at three selected forest reserves, namely Terla A, Bertam and Bukit Bujang Forest Reserves in Cameron Highlands, Peninsular Malaysia to assess the potential of recording montane bird species at lower strata using camera traps. In general, Enicurus schistaceus, Arborophila campbelli and Rhipidura albicollis were the most recorded camera trap images. This survey recorded 16 diurnal and one nocturnal bird species. These preliminary findings demonstrated the potential of using a non-invasive method to assess understory bird species in montane habitats, which may complement other survey methods.